A guideline of determination haram status of intentionally adding animal plasma in surimi products - Mohd Sukri, Siti Jamilah; Mat Jubri@Shamsuddin, Mustafa; Ramli, Mohd Anuar; Rohman, Abdul; Sutoyo, Suyatno; Ahmad Fadzillah, Nurrulhidayah (Penerbit UTM Press, 2022)
The process of intentionally adding animal plasma additive (APA) into surimi products is part of the polemic issues are getting attention among Muslim consumers. APA possesses good functional properties such as improving emulsifying capacity, alternative for fat, alternative for eggs besides functions as a cheap protein alternative. There are opinion regards transformation of animal plasma into commercial APA is part of the sustainable effort to minimize environmental problems as a result the non-systematic disposal of animal blood into land and water. Moreover, some of the minor group of scholars claimed the prohibition attributes to spilled-out blood not the plasma which has transformed its physical characteristics. However, based on the collected qualitative data from numerous library sources and interview with the experts show that there is no room to permit its utilization unless in dharuriyh situation. To justify the arguments, the researchers propose a guideline of determination haram status animal plasma into surimi products that will be a good reference for other researchers to comprehend this issue. The analysis shows ‘illah (legal cause) of its prohibition due of its impurity characteristics as stated in the Islamic legal texts. In addition, principle of Istihalah, Istihlak , Bara’ah Asliyyah and preservation of dharuriyyah al- khamsah are applied to strengthen the arguments. Last but not least, to vast up the discussion, fatwa debates related to the status of APA at International and National level are included as well. Lastly, this guideline has potential to contribute in Contemporary fiqh and science knowledge, halal seafood producer and advancement of future research particularly in the context to understand hukm of intentionally transform and mixing APA as an alternative ingredient into surimi products.